2020
DOI: 10.3390/ijfs8040059
|View full text |Cite
|
Sign up to set email alerts
|

Candlestick—The Main Mistake of Economy Research in High Frequency Markets

Abstract: One of the key problems of researching the high-frequency financial markets is the proper data format. Application of the candlestick representation (or its derivatives such as daily prices, etc.), which is vastly used in economic research, can lead to faulty research results. Yet, this fact is consistently ignored in most economic studies. The following article gives examples of possible consequences of using candlestick representation in modelling and statistical analysis of the financial markets. Emphasis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The articles ( Li et al, 2021 ; Yu, Wang & Lai, 2008 ) demonstrated that timescale decomposition is an actual efficient method that followed the “divide-and-conquer” approach. For example, the divide-and-conquer approach has been used in several fields: oil prices ( Rădulescu et al, 2020 ; Wang et al, 2018 ) foreign currency exchange rate ( Jin et al, 2021 ; Lin, Chiu & Lin, 2012 ; Wang & Luo, 2021 ), stock market trend ( Cheng & Wei, 2014 ; Na & Kim, 2021 ; Stasiak, 2020 ; Wang & Luo, 2021 ), wind speed ( Hu et al, 2021 ; Wang et al, 2014 ; Xie et al, 2021 ), electronics sales ( Chen & Lu, 2021 ; Lu & Shao, 2012 ), healthcare ( Aileni, Rodica & Valderrama, 2016 ; Dwivedi et al, 2019 ; Singh, Dwivedi & Srivastava, 2020 ), and tourism market ( Chen, Lai & Yeh, 2012 ; Guerra-Montenegro et al, 2021 ; Tang et al, 2021 ). The hybrid EMD combined with the artificial neural network(ANN) method was applied to predict the first, second, and third steps moving forward wind speed time series ( Chen et al, 2021 ; Hu et al, 2021 ; Liu et al, 2012 ; Liu, Hara & Kita, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The articles ( Li et al, 2021 ; Yu, Wang & Lai, 2008 ) demonstrated that timescale decomposition is an actual efficient method that followed the “divide-and-conquer” approach. For example, the divide-and-conquer approach has been used in several fields: oil prices ( Rădulescu et al, 2020 ; Wang et al, 2018 ) foreign currency exchange rate ( Jin et al, 2021 ; Lin, Chiu & Lin, 2012 ; Wang & Luo, 2021 ), stock market trend ( Cheng & Wei, 2014 ; Na & Kim, 2021 ; Stasiak, 2020 ; Wang & Luo, 2021 ), wind speed ( Hu et al, 2021 ; Wang et al, 2014 ; Xie et al, 2021 ), electronics sales ( Chen & Lu, 2021 ; Lu & Shao, 2012 ), healthcare ( Aileni, Rodica & Valderrama, 2016 ; Dwivedi et al, 2019 ; Singh, Dwivedi & Srivastava, 2020 ), and tourism market ( Chen, Lai & Yeh, 2012 ; Guerra-Montenegro et al, 2021 ; Tang et al, 2021 ). The hybrid EMD combined with the artificial neural network(ANN) method was applied to predict the first, second, and third steps moving forward wind speed time series ( Chen et al, 2021 ; Hu et al, 2021 ; Liu et al, 2012 ; Liu, Hara & Kita, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The candlestick chart has many functional visual patterns and can interpret prices during the session simply so that it is easy to explain in decision-making. As a result, the candlestick chart is one of the most widely used charts [3,4].…”
Section: Introductionmentioning
confidence: 99%